Phylogeny and morphology of Helicotubeufia gen. nov., with three new species in Tubeufiaceae from aquatic habitats - J. K. Liu (2018)
© Guizhou Academy of Agricultural Sciences. We are participating in an investigation of freshwater fungi along a north-south latitudinal gradient in the Asian region. Five new collections of asexual and sexual morphs of Tubeufiaceae from decaying wood in freshwater streams were obtained from China and Thailand. Morphologically, they line well with Tubeufiaceae in having superficial, solitary, scattered, subglobose to ellipsoidal-ovate, dark brown to black ascomata; cylindrical asci with hyaline, fusiform, multi-septate, slightly curved and guttulate ascospores and hyphomycetous helicosporous asexual morphs. Phylogenetic analyses based on combined LSU, ITS and TEF1α sequences data indicate that they formed a monotypic clade among the genera of Tubeufiaceae, but as a phylogenetically distinct lineage. Therefore, we introduce a new genus Helicotubeufia gen. nov, with three species (H. guangxiensis, H. hydei and H. jonesii) to accommodate these new taxa. Detailed descriptions and illustrations are provided, as well as the comparisons with similar taxa.